Effect of Fe‐Contained Species on the Preparation of α‐Si3N4 Fibers in Combustion Synthesis. Issue 4 (1st February 2016) - Ge, Yiyao; Sun, Siyuan; Wang, Qi; Cui, Wei; Zou, Yifeng; Xie, Zhipeng; Chen, Kexin
Abstract : Herein, Si3 N4 powders of comparatively high α‐phase but with distinct morphologies, especially α‐Si3 N4 fibers, were successfully prepared by a developed combustion synthesis (CS) strategy. Different proportions of Fe and Fe2 O3 were innovatively doped in reactants as additives to control the phase constitution and their relative percentage, as well as morphologies of final microstructures. One step further, the effects of Fe‐contained impurities on the CS process were rationally proposed and verified based on a series of meticulous designed experiments. It turns out that two contradictory effects of metal Fe on the formation of α‐Si3 N4 synergistically play vital roles in the CS reaction. The existence of metal Fe can accelerate the crystallization of the amorphous SiO2, which act as protection layer outside the Si powders and subsequently promote the generation of gaseous SiO. These gaseous SiO easily reacts with N2 and eventually form α‐Si3 N4 . On the other hand, the formation of β‐Si3 N4 will be promoted by the assistance of some liquid phases, and in this case, they mainly come from the reaction between Fe and Si. For this study, when the content of doped Fe is below 2 mol%, the prior effect on promoting α‐phase content is pronounced. Otherwise, the latter dominates the CS process as the content of Fe additive is further increased above 2 mol%. In a different way, Fe2 O3 mainly encourages the formation of β phase through the large amount of newly generated liquid phases, although the reduced SiO2 and Fe may still promote the α/β ratio on some extent.